RESPON PETANI TERHADAP KUALITAS KINERJA PENYULUH DI DESA TUNFEU KECAMATAN NEKAMESE KABUPATEN KUPANG - Satria A. A. Bentura; Leta Rafael Levis; Lika Bernadina (Undana Press, 2023)
The purpose of this study is to find out the performance of extension workers in Tunfeu village in empowering farmers, then to find out the response of farmers to the quality of extension performance in Tunfeu village. The population in this study was a member of a farming group that developed various types of farming, respondents totaling 99 people selected by census. The type of data used are primary data and secondary data. The results of this study show that. 1). A contributing factor in the performance of Agricultural extensionists in empowering farmers in Tunfeu village is the role of extension workers as educators, consultants, informants, escorts and mentors.. Then the following is 2). The response of farmers to the quality of extension performance in Tunfeu village in this study was in the category of